When Novelty Skips the Feel-Good: Dual Behavioural Routes of Product Creativity and Social Ambience in Creative Tourism - Mohd Fahmi, Yahaya (2026)
Creative tourism theory assumes that creative stimuli shape travellers’ behavioural intentions only after being filtered through experience quality (EQ), yet empirical tests of this mechanism are scarce. Re-analysing a Malaysian dataset of 499 respondents, this study uncovers a dual route pattern in which some creative cues operate through EQ, while product novelty also acts directly on behaviour. Using variance-based SEM with a parallel multiple mediation design, two creative stimuli were examined: Creative Product (Novelty and Usefulness) and Press (Physical and Social ambience), with EQ decomposed into its experiential facets. Results show that Press Social is the most influential indirect driver of behavioural intention, as it amplifies EQ which subsequently enhances intention. By contrast, Product Novelty exerts a direct effect in addition to a smaller mediated path, suggesting that novelty can stimulate action even without changes in affective appraisal. An ImportancePerformance Map highlights Press Social as the highest leverage lever, while Novelty represents a low importance but high opportunity factor.